2021
DOI: 10.3390/metabo11070455
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and Dual RNA-Sequencing on Root Nodules Revealed New Cellular Functions Controlled by Paraburkholderia phymatum NifA

Abstract: Paraburkholderia phymatum STM815 is a nitrogen-fixing endosymbiont that nodulate the agriculturally important Phaseolus vulgaris and several other host plants. We previously showed that the nodules induced by a STM815 mutant of the gene encoding the master regulator of nitrogen fixation NifA showed no nitrogenase activity (Fix−) and increased in number compared to P. vulgaris plants infected with the wild-type strain. To further investigate the role of NifA during symbiosis, nodules from P. phymatum wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Out of all detected metabolites, we focused on the ion counts belonging to IAM and IAA. As we previously reported, plants inoculated with P. phymatum wild-type produced significantly higher amounts of IAM and IAA than non-inoculated plants (Bellés-Sancho et al, 2021a), while the levels of these two auxins in the nifA mutant were found elevated compared to the wild-type nodules (Figure 5; Bellés-Sancho et al, 2021a). The amount of IAM and IAA in nodules induced by the single iaaMH and double nifA-iaaMH mutant decreased to the same levels as observed in non-inoculated roots, suggesting that bacterial auxin production accounted for the main portion of IAA and IAM found in wild-type and nifA nodules (Figure 5).…”
Section: Paraburkholderia Phymatum Iaamh Genes Are Essential For the ...supporting
confidence: 79%
See 4 more Smart Citations
“…Out of all detected metabolites, we focused on the ion counts belonging to IAM and IAA. As we previously reported, plants inoculated with P. phymatum wild-type produced significantly higher amounts of IAM and IAA than non-inoculated plants (Bellés-Sancho et al, 2021a), while the levels of these two auxins in the nifA mutant were found elevated compared to the wild-type nodules (Figure 5; Bellés-Sancho et al, 2021a). The amount of IAM and IAA in nodules induced by the single iaaMH and double nifA-iaaMH mutant decreased to the same levels as observed in non-inoculated roots, suggesting that bacterial auxin production accounted for the main portion of IAA and IAM found in wild-type and nifA nodules (Figure 5).…”
Section: Paraburkholderia Phymatum Iaamh Genes Are Essential For the ...supporting
confidence: 79%
“…In analogy to lateral root development, such sites might be genetically or hormonally primed to respond to internal auxin signaling. To confirm that the nodular levels of auxinics we previously measured (Bellés-Sancho et al, 2021a) originated from bacterial production under NifA-IaaMH regulation, we estimated the amount of indolics in our strains after planktonic growth (Figure 7F). In comparison to wild-type P. phymatum that produced traces of indolics, the nifA mutant synthetized considerable amounts (37.9 µg/ml).…”
Section: Nifa-dependent Clustering Of Phaseolus Vulgaris Nodules Is I...mentioning
confidence: 72%
See 3 more Smart Citations